The appeals and level of involvement influencing purchasing decision - Matušínská Kateřina; Stoklasa Michal (Management şi Marketing, 2022)
The aim of this paper is to find out how various product categories are influenced by rational or emotional appeals and the level of involvement in purchasing decisions with regard to selected demographic characteristics of Czech consumers. Scientific research is based on the theoretical assumptions of the Foote-Cone-Belding (hereafter FCB) model with newly formulated product categories that correspond to current Czech consumer behavior. The theoretical background of the paper covers the knowledge of cognitive consumer choice principles with emphasis on different appeals and a level of involvement within consumer decision. Primary research data were obtained using a questionnaire, on the online panel of research agency Ipsos, on 1,050 Czech respondents. The methods used are modified FCB grid based on previous research study, Kolmogorov-Smirnov test, Kruskal-Wallis test with a post hoc test using Dunn’s test with Bonferroni correction, and positional maps. The results reveal not only how the newly defined product categories are influenced by rational or emotional appeals and high or low involvement, but also the differences of the theoretical FCB model in comparison with its practical implementation. It is necessary to adapt (extend) this model according to the specific conditions and identification features of different segments. The newly introduced transformed nine-quadrants concept of the FCB model is proposed to be applied.